Obesity-induced ocular changes in children and adolescents: A review - Dezor-Garus, Julia; Niechciał, Elżbieta; Kędzia, Andrzej; Gotz-Więckowska, Anna (Frontiers in Pediatrics, 2023)
Childhood obesity has reached epidemic levels worldwide. Overweight and obesity is associated with an increase in several inflammatory markers, leading to chronic low-grade inflammation responsible for macro- and microvascular dysfunction. While the impact of obesity on overall health is well-described, less is known about its ocular manifestations. Still, there are few studies in children and adolescents in this regard and they are inconsistent. However, some evidence suggests a significant role of overnutrition in the development of changes in retinal microvasculature parameters (wider venules, narrower arterioles, lower arteriovenous ratio). Higher values of intraocular pressure were found to be positively correlated with high body mass index (BMI) as well as obesity. In addition, the retinal nerve fiber layer (RNFL) values seem to be lower in obese children, and there is a significant negative correlation between RNFL values and anthropometric and/or metabolic parameters. Changes also could be present in macular retinal thickness and choroidal thickness as well as in the retinal vessel density in children with obesity. However, these associations were not consistently documented. The purpose of this review is to present the most current issues on child obesity and the related potential ocular effects through an overview of international publications from the years 1992-2022.